PENGARUH ORIENTASI ETIKA, KOMITMEN PROFESIONAL, KOMITMEN ORGANISASI, DAN SENSITIVITAS ETIS TERHADAP INTERNAL WHISTLEBLOWING (Studi Empiris Pada SKPD Kota Pekanbaru) - Wimpi Abhirama Janitra; Hardi '; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to know the influence of the Idealism Ethical Orientation, Relativism Ethical Orientation, professional commitment, Organizational Commitment and Ethical Sensitivity to the Internal Whistleblowing. The main problem that researchers descriptions are as follows: to see how many significant relationship between the dependent variable to the independent varaibel.This research was conducted on employees SKPD Pekanbaru city. This research was included in the quantitative research. The type of data used in this research is the primary data by source. And then, in data collections sampling was conducted with a purposive sampling method (Sugiyono, 2012: 392) with respondents as many as 88 employees who working in SKPD Pekanbaru city. Data were analyzed using multiple regression with SPSS version 20. The results of this research showed that the Idealism Ethical Orientationhave influnce to the Internal Whistleblowing, Relativism Ethical Orientationhave influnce to the Internal Whistleblowing, professional commitmenthave influnce to the Internal Whistleblowing, Organizational Commitment have influnce to the Internal Whistleblowing, and Ethical Sensitivity have influnce to the Internal Whistleblowing. And the conclution in this research are all the hypotheses presented in this research received.Keywords : Internal Whistleblowing, ethical orientation, professional commitment, organizational commitment, and ethical sensitivity.